PREVALENSI DAN HUBUNGAN SINDROM METABOLIK DENGAN PENYAKIT GINJAL KRONIK PADA POPULASI DESA LEGIAN, KUTA BALI - Ayu, Paramita; Kandarini, Yenny; Widiana, G Raka; Sudhana, W; Loekman, Jodhi S; Suwitra, K (journal of internal medicine; Vol. 12, No. 2 Mei 2011)
Metabolic syndrome may relate to pathogenesis of chronic kidney disease (CKD). There is scarce data with regard to that phenomenon in Indonesian general population. We conduct a study to determine the prevalence of metabolic syndrome and its relationship with CKD individuals in general population of Legian Village, Bali. An analytical cross sectional study was carried out in the community of Legian Village, a tourist destination in Bali. Samples were selected through simple random sampling. Two hundred and eighty four samples (117 males and 107 females, aged 46.1 ± 10.02 years) were included. Prevalence of hypertension, hypertrigliseridemia, hypoHDL-cholesterol, central obesity, impaired fasting glucose (IFG), obese and CKD was 14.1%, 38.4%, 25%, 18%, 11.6%, 51.8% and 11.6% respectively. Using bivariate analysis, there were strong and significant relationship between hypertension (OR 2.6, 95%CI 1.12 to 6.19, p = 0.02) and IFG (OR 5.21; 95%CI 2.23 to 12.13, p = 0.00) with CKD. Using multivariate logistic regression entering those components of metabolic syndrome into the model, it was consistently found that hypertension and DM is the associated factors for CKD in the population. There was increasing odds of CKD about 1,0-fold every augment of metabolic syndrome components (OR 1.098; 95%CI 0.83 to 1.44). As our conclusion, hypertension and IFG are associated factor for CKD in general population. Multiple components increased risk factor for CKD.
Keywords: metabolic syndrome, chronic kidney disease, general population